THE LAW OF INSEPARABLE CONNECTION OF DUALITY OF THE SYSTEMS (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The formula for the composition, structure and form of entity of systems, expressedin physical quantities, shows the presence of two substances within them: materialistic substantialenergy in the envelope of space and non-materialistic entropy-informational in the envelope oftime. They are in conjunction relationship with each other, i.e. between them there is a necessaryconstant continuity, characteristic of the law of nature. The previously unknown law of nonseparableduality of systems was discovered, which applicable for all classes of systems: physical, biologicaland social, and therefore it belongs to the category of general – universal and fundamental laws ofthe Universe.
Keywords: law, substance, material, immaterial, duality, continuity.